Ação fisiológica da piraclostrobina na assimilação de CO2 e na atividade de enzimas antioxidantes em plantas de feijão em diferentes tensões de Água no solo - Jadoski, Cleber Junior [UNESP]; Rodrigues, João Domingos [UNESP]; Soratto, Rogério Peres [UNESP]; dos Santos, Claudiana Moura; Ribeiro, Essione (My University, 2015)
The objective of this study was to evaluate the effects of different levels of pyraclostrobin on bean (Phaseolus vulgaris L.) plants under different soil water tensions, on carboxylate parameters, on the activity of enzymes related to combat reactive oxygen species (ROS) and on grain yield. Randomized blocks in a split-plot design were used with three replicates. Plots consisted of four tensions (-10, -20, -30 and - 40 kPa) in which four doses of pyraclostrobin (0, 0.050, 0.075 and 0.1 L ha-1 a.i.) were tested at the beginning of the reproductive stage R5. Tensions of -10 and -20kPa did not lead to water stress. Tensions of -30 and -40kPa reduced carboxylative activity, lowered enzymatic efficiency and yield. Pyraclostrobin affected positively the antioxidative and carboxylative mechanisms as well as grain yield in tensions of -20 and -40 kPa.
Physiological action of piraclostrobin on CO2 assimilation and antioxidant enzime activity in bean plants at different soil water tensions
Keywords: Free radicals; Photosynthesis; Strobilurin; Water deficit